GDSS for Selecting Culinary Tourism in Bali Using Profile Matching and Borda - Sugiartawan, Putu; Wardani, Ni Wayan (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2023)
This research proposes a method for determining the best culinary tourism destinations in Bali. Currently, being able to determine the best and potential destinations is a problem for people who want to travel tourism in Bali, both domestic and foreign people. Factors that have a dominant influence in determining potential destinations that still cannot be determined with certainty. This will greatly affect the results of decisions that will be taken by the community in determining the destination to be chosen. For this reason, it is very important to create a model to determine the best destination that can be chosen by the community as a decision support system in making decisions. In this journal Profile Matching has been used to determine the best destination as a category that can be obtained from the rating shown on the selected destination.